As duas transições futuras: católicos, protestantes e sociedade na América Latina = The two future transitions : catholics, Protestants and Society in Latin America - Freston, Paul (Ciencias sociales y religión, 2010)
As a cumulative result of changes in the religious profile of Latin America in recent decades, the article foresees the approach of two major transitions, one Catholic and the other Protestant, in which relations between religion, state and society will be greatly modified. The Catholic transition (which may not happen in all countries of the region) refers to the tipping point at which the old socio-political roles become unsustainable. Multidimensional pluralism, numerical decline, relative institutional weakness, and the effects of democracy and the fragmenting of civil society will lead to a loss of ‘churchly’ status. In some countries, a symbolically important moment will be when the percentage of those who declare themselves Catholic falls below half of the population. Nevertheless, besides the Catholic transition there will also be a Protestant transition, which refers to the fact of a coming ceiling on Protestant growth and political aspirations. When this levelling off occurs, the nature of Latin American Protestantism will change radically, as will its relations with society, with politics and with the other religions. The article also argues for a more prominent place for Latin America in global debates on religion and modernity, since it represents a historically new evolutionary pattern for an old Christendom.